Pengetahuan Orang Tua Tentang Covid-19 dan Perkembangan Psikososial Anak Usia Sekolah - Blasius Perang (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Introduction: The Covid-19 pandemic created mass hysteria and uncertainty that gave rise to infodemics and fears in society, especially children, as one of the vulnerable populations. This makes a child's psychosocial disorder. Objective: This study was conducted to determine the relationship between parents' knowledge about covid-19 and the psychosocial development of school-age children. Method: The design of this study is analytical observational with a Crossectional Study approach. Sampling was carried out using nonprobability sampling techniques, especially consecutive selection with a sample size of 40 respondents, namely school-age children. The instrument used to measure research variables is the form of a closed questionnaire. Data processing was performed with SPSS version 24 and using chi-square statistical tests. Results: The results were obtained that the value of p = 0.002 with α = 0.05 showed a correlation between the old man's knowledge about Covid-19 and the child's psychosocial development. Conclusion: There is a positive relationship between parents' knowledge of Covid-19 and the psychosocial development of children